En-prime Subacts over Monoids with Zero - Dakheel , Shireen O. (Iraqi Journal of Science, 2022)
Throughout this paper S will be denote a monoids with zero. In this paper, we introduce the concept of En- prime subact, where a proper subact B of a right S- act As is called En- prime subact if for any endomorphism f of As and a As with f(a)S⊆ Bimplies that either a B or f(As) ⊆ B. The right S-act As is called En-prime if the zero subact of As is En-prime subact. Some various properties of En-prime subact are considered, and also we study some relationships between En-prime subact and some other concepts such as prime subact and maximal subact.